2015
DOI: 10.1016/j.conbuildmat.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation and fire behaviour of thermal insulation materials based on food crop by-products

Abstract: Natural thermal insulation materials developed from renewable crop by-products and natural binders are analysed in terms of their thermal degradation and fire behaviour. A pyrolysis combustion flow calorimetre (PCFC) is used to characterise some kinds of crop by-products, including rice husk, corn pith and barley straw. This technique is complemented with a TG analysis. Six thermal insulation materials, formulated with such crop by-products and two kind of natural binders, corn starch and sodium alginate, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…The onset temperature T0 (defined here as the temperature at which HRR reaches 10 W/g) was almost 100ºC higher than non-treated boards as the initial shoulder was displaced to the right, the PHRR was reduced more than three times and the mass loss was lower. Alginate showed a significant improvement, in agreement with the results previously found [Palumbo 2015], although it was moderate compared with boric acid. The addition of ammonium polyphosphate resulted in a 25% reduction of the peak heat release and a displacement of the initial shoulder to the right.…”
Section: Flaming Combustion Analysissupporting
confidence: 82%
See 4 more Smart Citations
“…The onset temperature T0 (defined here as the temperature at which HRR reaches 10 W/g) was almost 100ºC higher than non-treated boards as the initial shoulder was displaced to the right, the PHRR was reduced more than three times and the mass loss was lower. Alginate showed a significant improvement, in agreement with the results previously found [Palumbo 2015], although it was moderate compared with boric acid. The addition of ammonium polyphosphate resulted in a 25% reduction of the peak heat release and a displacement of the initial shoulder to the right.…”
Section: Flaming Combustion Analysissupporting
confidence: 82%
“…In previous work it was found that corn pith-alginate composites presented a remarkable propensity to smouldering combustion [Palumbo 2015]. Although fire reaction tests yielded good results, even for non-treated specimens, as they showed a self-extinguishing behaviour, after flame extinction a slow smouldering process proceeded until the complete consumption of the specimens.…”
Section: Smouldering Combustion Analysismentioning
confidence: 99%
See 3 more Smart Citations